Design and Performance Analysis of a Single-Phase BLDC Motor - Orhan, Ahmet; Yildiz, Sedat (Mdpi, 2026)
In today's world, the demand for compact, high-efficiency, and low-cost motors plays a significant role in the design of low-power electric machines. In combi fan applications, single-phase brushless direct current (BLDC) motors are generally preferred. Although these motors offer efficient and compact solutions, the occurrence of dead points at certain rotor positions creates a serious disadvantage that may prevent the motor from initiating motion. In this study, an asymmetric air gap design is proposed for a single-phase BLDC motor to eliminate the dead point problem and increase starting torque. The motor's performance has been evaluated through analytical calculations and two-dimensional finite element analysis (FEA) conducted using ANSYS Electronics Desktop 2020 R2 (Maxwell) software. The results show that the asymmetric air gap effectively eliminates the dead point and improves the motor's starting performance. However, torque ripple is still identified as a design parameter that must be considered. The scope of this study is not limited to single-phase BLDC motors; it also provides analytical approaches that can be applied to different electric motor designs, contributing to engineering applications in this field.
Keywords: ANSYS Maxwell; asymmetric air gap; dead point elimination; finite element analysis (FEA); single-phase BLDC motor